Perbandingan tumbuh kembang anak toddler yang diasuh Orang tua dengan diasuh selain orang tua - Widya - Fristi; Ganis - Indriati; Erwin - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Growth and development of child will be different between parent’s care and other’s care. The aim of this research was to determined the differences of growth and development of toddler who cared by parents and cared by others. Design of this research was analytic comparative. This research had been done in Sidomulyo Barat, Tampan district with 84 respondents, using cross sectional approach. The samples were taken by cluster sampling technique. The instruments are scales and gauges to the measure of weight and height, whereas to development of child used Denver Development Screening Test (DDST). Analysis data used univariate and bivariate analysis. Characteristic of respondents was analyzed by univariate and correlation between variables was analyzed by chi-square test. The results showed that there was differences between parent’s care and other’s care. Toddlers who cared by parent have better growth and development than care by others (p value < α). This research recommends to parents or child care provider to provide a good care, so the children will having growth and development optimally. Keywords : growth, development, toddler, parent’s care, other’s care